Kompetensi Sekretaris Mengelola Jadwal Kegiatan Pimpinan dengan Google Calendar di Fakultas Kedokteran Gigi Universitas Gadjah Mada - Yohannes Suraja; Yolanda Elisabeth Tamba (STARKI, 2023)
Abstract The secretary has various activities to assist the leader. One of the tasks of the secretary is to manage the leader’s schedule of activities. In the current era of information and communication technology, secretary must has competence in managing the leader’s schedule of activities with the Google Calendar (GC) application. This study aims to find out and describe the competence of the secretary to manage the leader’s schedule of activities with the GC applications at the Faculty of Dentistry, Gadjah Mada University. The secretary of the Faculty of Dentistry UGM leader has the competence to manage the leader’s schedule of activities with the GC application including knowledge of management practices, skills in using technology and information devices, self-development abilities, personality in communication skills and in attitudes and behavior. Abstrak Sekretaris mempunyai aneka kegiatan untuk membantu pimpinan. Salah satu tugas sekretaris yaitu mengelola jadwal kegiatan pimpinan. Pada era teknologi informasi dan komunikasi sekarang, sekretaris harus memiliki kompetensi pengelolaan jadwal kegiatan pimpinan dengan aplikasi Google Calendar (GC). Penelitian ini bertujuan ingin mengetahui dan mendeskripsikan kompetensi sekretaris mengelola jadwal kegiatan pimpinan dengan aplikasi GC di Fakultas Kedokteran Gigi Universitas Gadjah Mada. Sekretaris pimpinan FKG UGM memiliki kompetensi mengelola jadwal kegiatan pimpinan dengan aplikasi GC meliputi pengetahuan praktik manajemen, keterampilan penggunaan perangkat teknologi dan informasi, kemampuan pengembangan diri dan kepribadian keterampilan berkomunikasi serta sikap dan perilaku yang baik.